Imprensa e poder político no Chile [manuscrito]: - Emmanuel dos Santos (2018)
In the context of the government of Popular Unity (UP) in Chile (1970-1973), the vehicles of mainstream press played an important role either for legitimizing or criticizing the project of the "Chilean road to socialism". Our work deals with the comparative analysis of the ways in which the vicissitudes of the UP government were represented, reported and discussed in two of the main newspapers of the Chilean press: La Nación and El Mercurio. We investigate how these periodicals constructed and articulated speeches about UP's political propositions and practices, thus acting with important political actors. Our study led us to understand how these discourses were both articulated in relation to the daily political struggle, and in the construction of images and representations around thematic axes such as: antimarxism, popular power, military and political power, revolution. Thus, the work puts in the foreground the importance of the mass media to the hegemonic disputes of the different political projects in conflict during the government of Salvador Allende